THE PROBLEM OF EVIL IN BUDDHISM - R P Sharma (Journal of Dharma, 1977)
Buddhism frankly admits the existence of both good and evil in the universe. But the existence of evil does not constitute the same problem to the Buddhists as to the theists. The problem of evil takes a different form in Buddhism because a Buddhist does not start with the theistic assumption that the world is creat- ed by a perfect Being. Instead, he accepts the fact of evil and argues on this basis that the world, with all its imperfections, can- not be called the creation of a perfect Being. The presence of evil, in the form of suffering, is a challenge to the Buddhists and their main task is how to overcome it. Prof. K.N. Jayatillake rightly observes" ...in general, the problem of evil for the Bud- dhists is to recognize evil as such, to look for its verifiable causes and by removing the causes eliminate evil as far as possible at all its levels of existence". 1 Thus, the problem of evil appears mainly as a life-problem in Buddhism. Let us examine the problem of evil in its different aspects in Buddhism.